Integration of Chronic Oncology Services in Noncommunicable Disease Clinic in Rural Rwanda - Robert Rutayisire (Ubiquity Press, 2020)
Background: In rural sub-Saharan Africa, access to care for severe non-communicable diseases (NCDs) is limited due to myriad delivery challenges. We describe the implementation, patient characteristics, and retention rate of an integrated NCD clinic inclusive of cancer services at a district hospital in rural Rwanda. Methods: In 2006, the Rwandan Ministry of Health at Rwinkwavu District Hospital (RDH) and Partners In Health established an integrated NCD clinic focused on nurse-led care of severe NCDs, within a single delivery platform. Implementation modifications were made in 2011 to include cancer services. For this descriptive study, we abstracted medical record data for 15 months after first clinic visit for all patients who enrolled in the NCD clinic between 1 July 2012 and 30 June 2014. We report descriptive statistics of patient characteristics and retention. Results: Three hundred forty-seven patients enrolled during the study period: oncology – 71.8%, hypertension – 10.4%, heart failure – 11.0%, diabetes – 5.5%, and chronic respiratory disease (CRD) – 1.4%. Twelve-month retention rates were: oncology – 81.6%, CRD – 60.0%, hypertension – 75.0%, diabetes – 73.7%, and heart failure – 47.4%. Conclusions: The integrated NCD clinic filled a gap in accessible care for severe NCDs, including cancer, at rural district hospitals. This novel approach has illustrated good retention rates.